A multiple linear regression in determining the influential factors of cashless payment adoption among university students / Nor Hazreeni Hamzah ...[et al.] - Hamzah, Nor Hazreeni; Ibrahim, Nur Safwati; Ibrahim, Nurul Bariyah; Mohamed Zukri, Shamsunarnie; Mohd Fauzi, Noor Zafarina; Azizan, Nurul Hafizah (Universiti Teknologi MARA, Kelantan, 2023)
The procedure of receiving and making payments has altered as a result of the development of mobile wallets and online payment options. Different sorts of payment methods have emerged as a result of ongoing technological and governmental developments. However, the adoption of cashless transactions in Malaysia was relatively slow due to a lack of awareness and confidence about security concerns. Hence, this study aims to determine the level of Adoption of Cashless Payment among university students. A total of 232 UiTM Cawangan Kelantan, Kampus Kota Bharu (UiTMKB) students were involved in the study using stratified sampling. Five factors had been examined which were Performance Expectancy, Social Influence, Perceived Technology Security, Perceived Ease of Use and Bedonie Motivation. The sn1dy revealed that all factors had a significant effect on the Adoption of Cashless Payment, with Social Influence as the most significant influence.